2011
DOI: 10.1088/2041-8205/728/2/l25
|View full text |Cite
|
Sign up to set email alerts
|

PROBING THE FAINT END OF THE QUASAR LUMINOSITY FUNCTION AT z ∼ 4 IN THE COSMOS FIELD

Abstract: We searched for quasars that are ∼ 3 mag fainter than the SDSS quasars in the redshift range 3.7 z 4.7 in the COSMOS field to constrain the faint end of the quasar luminosity function. Using optical photometric data, we selected

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
109
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(130 citation statements)
references
References 48 publications
17
109
4
Order By: Relevance
“…To compare these data at z=4 with our results, we computed the Chandra COSMOS-Legacy space density in two redshift bins at z= [3.5-4.5] where L-COSMOS3 is not complete (see Figure 9); therefore, these two data points should be treated as lower limits. We found that our data are in good agreement with the result obtained by Glikman et al (2011), while the estimates by Ikeda et al (2011) lie below our estimates by a factor of ∼2-3. However, it is worth noting that both of these optical surveys are sampling unobscured Type 1 AGNs, while in L-COSMOS3 a significant fraction of obscured objects is also taken into account.We will discuss the agreement between the optical surveys and our Type 1 AGN population space density in the next section.…”
Section: 55supporting
confidence: 91%
See 1 more Smart Citation
“…To compare these data at z=4 with our results, we computed the Chandra COSMOS-Legacy space density in two redshift bins at z= [3.5-4.5] where L-COSMOS3 is not complete (see Figure 9); therefore, these two data points should be treated as lower limits. We found that our data are in good agreement with the result obtained by Glikman et al (2011), while the estimates by Ikeda et al (2011) lie below our estimates by a factor of ∼2-3. However, it is worth noting that both of these optical surveys are sampling unobscured Type 1 AGNs, while in L-COSMOS3 a significant fraction of obscured objects is also taken into account.We will discuss the agreement between the optical surveys and our Type 1 AGN population space density in the next section.…”
Section: 55supporting
confidence: 91%
“…The limitation of optical surveys is that at low optical luminosities (−24.5  M AB  −22), the standard color-color quasar identification procedures become less reliable because stars can be misinterpreted as quasars. As a result, low-luminosity AGN luminosity functions from optical surveys are so far in disagreement (e.g., Glikman et al 2011;Ikeda et al 2011;Masters et al 2012). Moreover, optical surveys are biased against obscured sources, whose contribution also becomes more significant at low luminosities (e.g., Ueda et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, Glikman et al (2011) claimed roughly a factor four more sources at z 3 than did Ikeda et al (2011). More recently, Masters et al (2012) found a decrease by a factor of four in the number density of faint QSOs in COSMOS between z ∼ 3.2 and z ∼ 4, supporting the results of Ikeda et al (2011). Overall, the results from Masters et al (2012) suggest a similar evolution of the UV and X-ray LFs at z 3.…”
Section: Observational Parametersmentioning
confidence: 55%
“…While different groups agreed on the faint-end slope of the LF, 1.7, they derived quite different absolute space densities. Specifically, Glikman et al (2011) claimed roughly a factor four more sources at z 3 than did Ikeda et al (2011). More recently, Masters et al (2012) found a decrease by a factor of four in the number density of faint QSOs in COSMOS between z ∼ 3.2 and z ∼ 4, supporting the results of Ikeda et al (2011).…”
Section: Observational Parametersmentioning
confidence: 65%
“…One high-redshift source (α = 150.35980δ = 2.0737081) is detected in the X-ray by Chandra in the C-COSMOS survey (Elvis et al 2009), though unlike the XMM survey of COSMOS the Chandra survey is not uniform over the entire field. Two of the LBG sources are point sources in ACS (α = 149.87082δ = 1.8827920, and α = 150.13036δ = 2.4660110 taken from Ikeda et al 2011), but show no signs of AGNs in their spectra, nor have X-ray detections.…”
Section: Redshift Agns and Lyα Identificationmentioning
confidence: 99%